Modeling the superstorm in the 24th solar cycle - Emre Eroglu (Earth, Planets and Space, 2019)
Abstract The St. Patrick’s Day phenomenon is a geomagnetic storm that deserves serious discussion because of its intensity and effectiveness. This study focuses on the St. Patrick’s Day storm on March 17, 2015, which is the first big storm of the 24th solar cycle. The data obtained from various spacecrafts observing the ionosphere reveal the reputation and the strength of the storm. The author tries to discuss the event as a whole with all its parameters. Variables of the study are the solar wind parameters and zonal geomagnetic indices. Models with solar wind pressure, proton density and magnetic field may aid in making the dynamic structure of the phenomenon more understandable. The obtained models are able to give the reader an idea of the results even if the storm prediction percentage is low. The author has endeavored to obey the cause–effect relationship without ignoring the physical principles when establishing mathematical models. Despite the fact that the relations between variables have poor correlation or have low statistical significance, in order to introduce the physical point of view they have not been ignored. This study puts forth a new mathematical perspective by discussing and visualizing what happened in the phenomenon.s